2019
DOI: 10.1007/s10648-019-09498-w
|View full text |Cite
|
Sign up to set email alerts
|

The Gamification of Learning: a Meta-analysis

Abstract: This meta-analysis was conducted to systematically synthesize research findings on effects of gamification on cognitive, motivational, and behavioral learning outcomes. Results from random effects models showed significant small effects of gamification on cognitive (g = .49, 95% CI [0.30, 0.69], k = 19, N = 1686), motivational (g = .36, 95% CI [0.18, 0.54], k = 16, N = 2246), and behavioral learning outcomes (g = .25, 95% CI [0.04, 0.46], k = 9, N = 951). Whereas the effect of gamification on cognitive learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
467
4
40

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 692 publications
(542 citation statements)
references
References 67 publications
31
467
4
40
Order By: Relevance
“…In contrast to some reports in the literature (e.g. Mekler et al, 2015;Sailer and Homner, 2020), this review provides convincing evidence in favor of positive behavioral and motivational outcomes on employees through gamification. Recent scholarship provides empirical evidence to suggest that the use of game design elements can improve HR practices and tools (e.g.…”
Section: Discussioncontrasting
confidence: 87%
“…In contrast to some reports in the literature (e.g. Mekler et al, 2015;Sailer and Homner, 2020), this review provides convincing evidence in favor of positive behavioral and motivational outcomes on employees through gamification. Recent scholarship provides empirical evidence to suggest that the use of game design elements can improve HR practices and tools (e.g.…”
Section: Discussioncontrasting
confidence: 87%
“…Gamification is a new concept and is said to foster students' motivation (e.g. Alsawaier 2018; Dichev & Dicheva 2017;Dreimane 2019;Hakulinen, Auvinen & Korhonen 2015;Hamari 2015;Koivisto & Hamari 2019;Pechenkina, Laurence, Oates, Eldridge & Hunter 2017;Sailer & Homner 2019;Utomo & Santoso 2015). This concept with its associated game mechanics was considered in this survey to foster students' learning motivation.…”
Section: Introductionmentioning
confidence: 99%
“…To remedy this problem, one of the most prominent instructional methods is through the gamification strategy. Researchers have acknowledged the values of gamification in influencing human behavior (Buckley & Doyle, 2016;Sailer & Homner, 2020), promoting engagement (Brophy, 2015;Rahman et al, 2018), generating motivation (Deterding et al, 2011;Hwang et al, 2015;Persico et al, 2019), promoting attractive competition (Huang et al, 2018), providing spontaneous immediate feedback (Bouchrika et al, 2019;Koivisto & Hamari, 2014), and enhancing students' learning achievement (Attali & Arieli-Attali, 2015;Buckley & Doyle, 2016;Yıldırım & Şen, 2019). Specifically, an enormous body of research has also indicated that game-based learning (GBL) instruction has significantly contributed to promoting students' language learning experience (Ataeifar et al, 2019;Klimova & Kacetl, 2018;Lee et al, 2016;Liu & Chu, 2010;Ma, 2017).…”
mentioning
confidence: 99%